Nonstandard young tableaux of \(Î“_1 \)â€“ non deranged permutation group \(G_p ^{Î“_1 }\) - Garba, Isah Abor; Ejima, Ojonugwa; Olalekan Aremu, Kazeem; Hamisu, Usman (Global Journal of Mathematical Analysis, 2017)
There is a link between the representation of the permutation group Â and the combinatorial object called Young tableaux. In this paper, we describe the representation of G1- non deranged permutation group via the Young tableaux, and we establish that every Young tableaux of this permutation group is not standard.